2018
DOI: 10.18843/ijms/v5i2(1)/13
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Smoothing & Implications of Lintner Model–A Study of Indian Consumer Goods Sector using Panel Data

Abstract: Dividend smoothing is the strategy used by the managers to target net earnings in the payout ratio as shareholders prefer stable dividend over volatile payments (Lintner 1956

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…The results were supported by Otieno and Oloo (2013) showed that profitability which includes the earnings after expenses, interest and taxes determined the dividend smoothing of the companies studied. Rane and AnjanaRaju (2018) found robust relationship between the smoothness of a firm's dividends with independent variable profitability and lagged dividend. The decision of a specific speed of change factor relies on potential varieties in net profit after expense.…”
Section: The Regression Model Is As Shown Belowmentioning
confidence: 91%
See 1 more Smart Citation
“…The results were supported by Otieno and Oloo (2013) showed that profitability which includes the earnings after expenses, interest and taxes determined the dividend smoothing of the companies studied. Rane and AnjanaRaju (2018) found robust relationship between the smoothness of a firm's dividends with independent variable profitability and lagged dividend. The decision of a specific speed of change factor relies on potential varieties in net profit after expense.…”
Section: The Regression Model Is As Shown Belowmentioning
confidence: 91%
“…The examination prescribed that if dividend smoothing is energized, it could prompt dividend based management of earning. Rane and AnjanaRaju (2018) Ability database kept by Center for Monitoring Indian Economy (CMIE) was the prime source of information for the examination reason. study finds robust relationship between the smoothness of a firm's dividends with independent variable profitability and lagged dividend.…”
Section: Empirical Reviewmentioning
confidence: 99%